2022
DOI: 10.1088/1361-648x/ac943f
|View full text |Cite
|
Sign up to set email alerts
|

Understanding magnetocrystalline anisotropy based on orbital and quadrupole moments

Abstract: Understanding magnetocrystalline anisotropy (MCA) is fundamentally important for developing novel magnetic materials. Therefore, clarifying the relationship between MCA and local physical quantities observed by spectroscopic measurements, such as the orbital and quadrupole moments, is necessary. In this review, we discuss MCA and the distortion effects in magnetic materials with transition metals (TMs) based on the orbital and quadrupole moments, which are related to the spin-conserving and spin-flip terms in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 79 publications
0
5
0
Order By: Relevance
“…By the discovery of perpendicular magnetic anisotropy (PMA), researchers have been prompted to readdress magnetic anisotropy with second-order anisotropy parameter ( K 2 ) owing to the contribution of uniaxial anisotropy. 10,11 There has been increased interest in magnetic multilayers due to the spatial fluctuations 10,12 that could contribute to the second-ordered anisotropy energy. 13 In both theory 14 and experiment, 15 K 2 signifies the easy axis along the surface normal to the film, but there are numerous other states that can be established by stabilizing the angle subtended between magnetization and the surface normal.…”
Section: Introductionmentioning
confidence: 99%
“…By the discovery of perpendicular magnetic anisotropy (PMA), researchers have been prompted to readdress magnetic anisotropy with second-order anisotropy parameter ( K 2 ) owing to the contribution of uniaxial anisotropy. 10,11 There has been increased interest in magnetic multilayers due to the spatial fluctuations 10,12 that could contribute to the second-ordered anisotropy energy. 13 In both theory 14 and experiment, 15 K 2 signifies the easy axis along the surface normal to the film, but there are numerous other states that can be established by stabilizing the angle subtended between magnetization and the surface normal.…”
Section: Introductionmentioning
confidence: 99%
“…Based on Bruno’s theory, the anisotropy of m orb corresponds to the stabilisation of PMA 32 . Interface PMA in 3 d TM ferromagnets is often discussed based on Bruno’s theory 3 , 10 , 33 35 . Thus, the increase in the interface PMA and interfacial m orb observed in Pt/Co/AlO x trilayers may also be linked to the large VCMA effect obtained at surface-oxidised Co/oxide interfaces.…”
Section: Introductionmentioning
confidence: 99%
“…10) On the basis of second-order perturbation theory, the MCA energy can be decomposed in terms of atomic-site, spin, and orbital contributions. [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] Bruno proposed that the spin-conserving terms between the occupied and unoccupied minority-spin states (↓ ↓ ) are related to the orbital magnetic moment observed experimentally. 11) Wang, Wu, and Freeman also showed that the spin-flip term between the occupied majority-spin states and unoccupied minority-spin states (↑ ↓ ) is connected with the quadrupole moment of the spin density.…”
mentioning
confidence: 99%
“…, where Q zz is the quadrupole moment of the electron-density distribution, S z is the z component of the spin angular momentum S, μ B is the Bohr magneton, ℏ is the reduced Planck constant, L is the orbital angular momentum, and L z is its z component. 13,14,16,17,23) Together with the orbital magnetic moment m orb , E MCA can be approximated as 16,23) ( )…”
mentioning
confidence: 99%
See 1 more Smart Citation